TLR9 Signaling Protects Alcohol-Induced Hepatic Oxidative Stress but Worsens Liver Inflammation in Mice - Hao, Liuyi; Zhong, Wei; Sun, Xinguo; Zhou, Zhanxiang (Frontiers in Pharmacology, 2021)
Toll-Like Receptor 9 (TLR9) elicits cellular response to nucleic acids derived from pathogens or dead cells. Previous studies have shown that TLR9-driven response may lead to differential impact on the pathogenesis of liver diseases. This study aimed to determine how TLR9 may contribute to chronic alcohol exposure-induced liver pathogenesis. We observed that TLR9 KO mice were more susceptible to alcohol-induced liver injury, which was evidenced by higher serum ALT/AST levels and more lipid accumulation in alcohol-fed TLR9 KO mice than wild-type mice. Alcohol-induced oxidative stress and mitochondrial dysfunction were also exacerbated by TLR9 KO. We found that chronic alcohol exposure-induced hepatic CHOP and ATF6 activation were enhanced in TLR9 KO mice. By using primary hepatocytes and AML-12 cells, we confirmed that TLR9 activation by CpG ODN administration significantly ameliorated acetaldehyde-induced cell injury via suppressing ATF6-CHOP signaling. By using STAT3 knockdown AML12 cells, we showed that TLR9-mediated STAT3 activation inhibited ATF6-CHOP signaling cascade and thereby protecting against acetaldehyde-induced mitochondrial dysfunction and cell injury. Interestingly, we found that TLR9 KO mice ameliorate chronic alcohol exposure-induced CXCL1 induction and neutrophils infiltration in the liver. Furthermore, hepatocyte lack of STAT3 significantly ameliorated CpG ODN and LPS-increased CXCL1 levels in hepatocytes. Overall, our data demonstrate that TLR9 signaling in hepatocytes counteracts alcohol-induced hepatotoxicity but worsens proinflammatory response.